Reversible Manipulation of Photoconductivity Caused by Surface Oxygen Vacancies in Perovskite Stannates with Ultraviolet Light. Issue 5 (17th December 2021) - Lee, Yujeong; Yoon, Daseob; Yu, Sangbae; Sim, Hyeji; Park, Yunkyu; Nam, Yeon‐Seo; Kim, Ki‐Jeong; Choi, Si‐Young; Kang, Youngho; Son, Junwoo
Abstract: Programmable optoelectronic devices call for the reversible control of the photocarrier recombination process by in‐gap states in oxide semiconductors. However, previous approaches to produce oxygen vacancies as a source of in‐gap states in oxide semiconductors have hampered the reversible formation of oxygen vacancies and their related phenomena. Here, a new strategy to manipulate the 2D photoconductivity from perovskite stannates is demonstrated by exploiting spatially selective photochemical reaction under ultraviolet illumination at room temperature. Remarkably, the ideal trap‐free photocurrent of air‐illuminated BaSnO3 (≈200 pA) is reversibly switched into three orders of magnitude higher photocurrent of vacuum‐illuminated BaSnO3 (≈335 nA) with persistent photoconductivity depending on ambient oxygen pressure under illumination. Multiple characterizations elucidate that ultraviolet illumination of BaSnO3  under low oxygen pressure induces surface oxygen vacancies as a result of surface photolysis combined with the low oxygen‐diffusion coefficient of BaSnO3 ; the concentrated oxygen vacancies are likely to induce a two‐step transition of photocurrent response by changing the characteristics of in‐gap states from the shallow level to the deep level. These results suggest a novel strategy that uses light–matter interaction in a reversible and spatially confined way to manipulate functionalities related to surface defect states, for the emerging applications using newly discovered oxide semiconductors. Abstract : Light–matter interaction under different oxygen pressure can reversibly manipulate photoconductivity from surface oxygen vacancies of perovskite stannate semiconductors. Utilizing surface‐selective photochemical reaction combined with the low oxygen‐diffusion coefficient, ultraviolet‐light‐excited electron–hole pairs of the perovskite compound under low oxygen pressure accelerate the unprecedented formation of spatially confined and optically programmable in‐gap states induced by oxygen vacancies at room temperature.